BRS Violeta (BRS Rúbea × IAC 1398-21) grape juice powder produced by foam mat drying. Part I: Effect of drying temperature on phenolic compounds and antioxidant activity - Maria de Carvalho Tavares, Iasnaia [UNESP]; Bonatto Machado de Castilhos, Maurício; Aparecida Mauro, Maria [UNESP]; Mota Ramos, Afonso; Teodoro de Souza, Reginaldo; Gómez-Alonso, Sergio; Gomes, Eleni [UNESP]; Da-Silva, Roberto [UNESP]; Hermosín-Gutiérrez, Isidro; Silva Lago-Vanzela, Ellen [UNESP] (Elsevier, 2019)
The BRS Violeta grape presents pulp and skin with high content of phenolic compounds (PCs) and intense purplish color. It was used as raw material for the production of juice and dehydrated products using foam mat drying at 60, 70 and 80 °C and freeze drying (control). HLPC-DAD-ESI-MSn allowed the evaluation of the quantitative and qualitative changes of the main PCs (anthocyanins, flavonols and hydroxycinnamic acid derivatives (HCAD)) present in the grapes during the processing. The use of the steam extraction method to obtain grape juice allowed a greater extraction of flavonols and, mainly derivatives of hydroxycinnamic acids, when compared with anthocyanins. Drying at 70 °C was the most suitable for the preservation of the PCs and, at the same time, for the reduction of the processing time. The powdered products presented considerable concentrations of total PCs (3–5 mg/g) and antioxidant activity (32–79 (DPPH) or 17–27 (FRAP) mg/g).
Keywords: 2-S-glutathionyl-trans-caftaric acid (PubChem CID: 71308212); Anthocyanins; Antioxidant activity; BRS Violeta grape; Delphinidin 3,5-diglucoside (PubChem CID: 10100906); Delphinidin 3-glucoside (PubChem CID: 443650); Flavonols; Foam mat drying; Hydroxycinnamic acid derivatives; Juice; Malvidin 3,5-diglucoside (PubChem CID: 44256978); Myricetin (PubChem CID:5281672); Myricetin 3-glucoside (PubChem CID: 44259426); Petunidin 3,5-diglucoside (PubChem CID: 10151874); Phenolic compounds; Quercetin 3-glucoside (PubChem CID: 44259229); trans-caftaric acid (PubChem CID: 13887348); trans-fertaric acid (PubChem CID: 72551457)